Acoustic Monitoring Enables Multi‐Taxa Conservation Assessment and Prioritisation Over Large Scales and for Rare and Cryptic Species - Adham Ashton‐Butt; Stuart E. Newson; Jeffrey W. Doser; Simon Gillings; Tatiana Kornienko; Viktar Fenchuk; James W. Pearce‐Higgins; Chris Scott; Philip W. Atkinson (Global Ecology and Biogeography, 2025)
Aim To combat the global biodiversity crisis, robust and scalable data are needed to target, monitor and evaluate conservation efforts, particularly in data‐poor regions and for cryptic taxa. Passive acoustic monitoring (PAM) has the potential to provide solutions, but real‐world examples are still rare. We demonstrate how PAM data can be used to rapidly and effectively map distributions of multiple taxa over large scales, in data‐poor regions. We show how these data can be used to assess the importance of existing protected areas and prioritise future conservation efforts, including for rare and cryptic species often neglected in such assessments. Location Global with a case study from Polesia, Eastern Europe. Time Period Present. Major Taxa Studied Bats, Birds, Small mammals and Bush crickets. Methods Using machine‐learning and manual verification, we identified bats, nocturnally active birds, small mammals and bush crickets from over 34,000 monitoring hours at 506 sites in the Polesia region of Belarus and Ukraine. Using multi‐species generalised mixed models in a Bayesian framework, we then predicted occupancy and acoustic activity for these species and their associations with protected areas, over a 151,000 km 2 project area. We identified areas of high conservation priority as measured by species richness and/or importance for globally or regionally threatened species. Main Conclusions Our approach provides a roadmap for collecting and processing large‐scale, multi‐taxa biodiversity data using passive acoustic monitoring. In our case study region, we show that although existing protected areas contain a relatively large proportion of high conservation priority areas, there are significant gaps in the protected area network. We also show low surrogacy of areas of high conservation priority between taxa at fine scales, but did at larger scales, showing the importance of multi‐taxa monitoring to prioritise protected areas that conserve a wide variety of species.

Genetics services in Latin America: a descriptive study of availability and utilization of genetics in healthcare - Ryan J. German; Erin Atkinson; Eric A. Storch; Claudia Soler-Alfonso; Sonia Margarit; Philip J. Lupo; Stacey Pereira (Journal of Community Genetics, 2025)

European Breeding Bird Declines Associated With Narrower Climatic Niches - Karolina Zalewska; James J. Gilroy; Inês Catry; Philip W. Atkinson; Alena Klvaňová; Aldina M. A. Franco (Journal of Biogeography, 2025)
Aim Anthropogenic climate change has increasingly been identified as a major threat to global biodiversity. However, the extent of this threat is likely to be uneven across species, due to differences in life histories or exposure to environmental change. The range of climatic conditions a species experiences across its range extent, known as the realised climatic niche, may be an indicator of species resilience to climate change. Species with large range extents, occurring across diverse climatic conditions, are expected to be less affected by climate change due to lower physiological constraints and tolerance to a wider range of climates. However, this may not be the case if local populations are adapted to specific environmental conditions. In this study, we investigate whether the extent of the species' realised climatic niche, also known as the climatic niche breadth, is linked to their long‐term population trends. Location Europe. Taxon Birds. Methods We extract climate data across the breeding‐only and resident ranges of 159 European bird species and use an ordination method to produce a representation of the species climatic niches. We then relate the niche breadth of each species to their range area and incorporate this relationship, along with the species' diet, main habitat type, migratory status and average body mass, to investigate their relationship with the species long‐term population trend. Results Species with small range areas showed larger variation in climatic niche breadth than species with larger ranges. For species with similar range areas, those with broader climatic tolerance were less likely to be declining than those with narrow climatic niches. Main Conclusions These findings can help us understand the threats associated with climate change and allow for rapid assessment of the importance of climatic factors on population trends, providing an invaluable tool for targeting habitat conservation.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Combining remote sensing and tracking data to quantify species' cumulative exposure to anthropogenic change - Claire Buchan; James J. Gilroy; Inês Catry; Chris M. Hewson; Philip W. Atkinson; Aldina M. A. Franco (Global Change Biology, 2023)
Identifying when and where organisms are exposed to anthropogenic change is crucial for diagnosing the drivers of biodiversity declines and implementing effective conservation measures. Accurately measuring individual‐scale exposure to anthropogenic impacts across the annual cycle as they move across continents requires an approach that is both spatially and temporally explicit—now achievable through recent parallel advances in remote‐sensing and individual tracking technologies. We combined 10 years of tracking data for a long‐distance migrant, (common cuckoo, Cuculus canorus ), with multi‐dimensional remote‐sensed spatial datasets encompassing thirteen relevant anthropogenic impacts (including infrastructure, hunting, habitat change, and climate change), to quantify mean hourly and total accumulated exposure of tracked individuals to anthropogenic change across each stage of the annual cycle. Although mean hourly exposure to anthropogenic change was greatest in the breeding stage, accumulated exposure to changes associated with direct mortality risks (e.g., built infrastructure) and with climate were greatest during the wintering stage, which comprised 63% of the annual cycle on average for tracked individuals. Exposure to anthropogenic change varied considerably within and between migratory flyways, but there were no clear between‐flyway differences in overall exposure during migration stages. However, more easterly autumn migratory routes were significantly associated with lower subsequent exposure to anthropogenic impacts in the winter stage. Cumulative change exposure was not significantly associated with recent local‐scale population trends in the breeding range, possibly because cuckoos from shared breeding areas may follow divergent migration routes and therefore encounter very different risk landscapes. Our study highlights the potential for the integration of tracking data and high‐resolution remote sensing to generate valuable and detailed new insights into the impacts of environmental change on wild species.

Landscape fires disproportionally affect high conservation value temperate peatlands, meadows, and deciduous forests, but only under low moisture conditions - Máire Kirkland; Philip W. Atkinson; James W. Pearce-Higgins; Mark C. de Jong; Thomas P.F. Dowling; Dmitri Grummo; Megan Critchley; Adham Ashton-Butt (Science of The Total Environment, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Spatio-temporal variations in the physiological profiles of streambed bacterial communities: implication of wastewater treatment plant effluents - Philips Akinwole; Amerti Guta; Madeline Draper; Sophia Atkinson (World Journal of Microbiology and Biotechnology, 2021)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

Information infrastructure for Australia’s Integrated Marine Observing System - Marton G. Hidas; Roger Proctor; Natalia Atkins; Julian Atkinson; Laurent Besnard; Peter Blain; Philip Bohm; Jon Burgess; Kim Finney; Dan Fruehauf; Guillaume Galibert; Xavier Hoenner; et al. (Earth Science Informatics, 2016)

Retraction Note: Patterns of bee diversity in mosaic agricultural landscapes of central Uganda: implication of pollination services conservation for food security - M. B. Théodore Munyuli; Philip Nyeko; Simon Potts; Phil Atkinson; Derek Pomeroy; Juliet Vickery (Journal of Insect Conservation, 2014)

RETRACTED ARTICLE: Patterns of bee diversity in mosaic agricultural landscapes of central Uganda: implication of pollination services conservation for food security - M. B. Théodore Munyuli; Philip Nyeko; Simon Potts; Phil Atkinson; Derek Pomeroy; Juliet Vickery (Journal of Insect Conservation, 2013)

Fuelling for the Sahara crossing: variation in site use and the onset and rate of spring mass gain by 38 Palearctic migrants in the western Sahel - Nicholas J. Bayly; Philip W. Atkinson; Stephen J. R. Rumsey (Journal of Ornithology, 2012)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Circadian variation in the circulatory responses to exercise: relevance to the morning peaks in strokes and cardiac events - Greg Atkinson; Helen Jones; Philip N. Ainslie (European Journal of Applied Physiology, 2010)

Transgenic Arabidopsis leaf tissue expressing a modified oryzacystatin shows resistance to the field slug Deroceras reticulatum (Müller) - Anthony J. Walker; Peter E. Urwin; Howard J. Atkinson; Philip Brain; David M. Glen; Peter R. Shewry (Transgenic Research, 1999)

The biodiversity and conservation of the birds of So Tom and Prncipe - Nicholas B. Peet; Philip W. Atkinson (Biodiversity and Conservation, 1994)